Malaysian Armed Forces staff readiness for knowledge management through the SECI-Model - Junizam bin Zainuddin (Kulliyyah of Education, International Islamic University Malaysia, 2017)
The 21st century revolution in military affairs is transcendently portrayed by a fast pace of technological change and the required transformation in doctrine and organization. Furthermore, the part of military personnel is evolving into that of 'knowledge workers'. The problem remains that there is inconsistency in retaining the tacit and explicit knowledge of transferred military personnel in addressing the knowledge management in the Malaysian Armed Forces (MAF).Those experiences, knowledge and skills are considered as intellectual properties and assets are seemed unprofitable and wasteful if they cannot be kept, stored and inherited within the organization. Organizations need to understand the degree of readiness among the staff before making commitment to providing the necessary policy supports and infrastructures to be involved with knowledge management (KM) activities and initiatives. The purpose of this quantitative method study is to investigate the concept of knowledge management (KM) readiness using intention to be involved in the KM process concept. These processes comprise Socialization, Externalization, Combination, and Internalization (SECI-model) as the theoretical framework of the study. The research also attempts to measure and validate the concept using data collected from 278 respondents consisting of MAF Education and Non-Education Staffs by using stratified sampling technique. The findings of the present research show that the high level of intention to be involved in KM processes through SECI model measured the KM readiness for both the MAF Education and Non-Education Staff which indicate that both the MAF Education and Non-Education staff are willing to be involved in each of the process within the revised model. The research also provides recommendation for the MAF Top Management, MAF Staff and further study.